Antioxidant Activity Test of Ethanol Extract of Sylissa carteri from the Waters of Poopoh Village, Minahasa Regency - Imanuela, Glorensia (PHARMACON, 2024)
Sponges are one of the marine biota that has great potential to produce active compounds. The metabolic process of the Stylissa carteri sponge can produce secondary metabolites. Secondary metabolite compounds produced by sponges have many benefits, one of which is as an antioxidant. This study aims to determine the antioxidant activity of the ethanol extract of the sponge Stylissa carteri obtained from the waters of Poopoh Village Minahasa Regency. The Stylissa carteri sponge was extracted by maceration method and using a solvent, namely ethanol. Testing of antioxidant activity was carried out using the DPPH (1,1-diphenyl-2- pikrihydrazyl) method which was measured using a UV-Vis Spectrophotometer. The results showed that the Stylissa carteri sponge extract had antioxidant activity with the highest inhibition percentage at a concentration of 100 ppm that is 78,2%.